Pinbox - Loh, Lester Kin Yi (2015)
My goal would be to design a proof-of-concept system with an array of mechanically controlled pins. 3D models made on a computer could be converted to data to be sent to this machine, which would then be recreated in physical space through the extrusion of these pins. The pins would be able to reset to their default positions after use, allowing the machine to be reusable. Users wishing to retain a permanent copy of the form generated by the machine would be able to do so by heat forming sheets of thermoplastics over the array.